Training on the Provision of Literacy Materials as Support Student Character during the Formation of the Pandemic - Umi Kulsum; Zainah Asmaniah; Deasy Aditya Damayanti; Ardi Mulyana; Nurul Hasan (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract The formation of students' character is doubtful for their success in learning during the current pandemic. Learning from home makes teachers limited in carrying out learning and building student character. One positive step is the School Literacy Movement. The success of this literacy activity will certainly succeed with the cooperation of teachers and parents to cultivate and provide literacy activities. This training focuses on the skills of teachers to digitize and use applications to provide literacy materials that can stimulate the formation of student character. The methods of implementing this training are introduction, training, practice, and simulation. The objects of this activity are the teachers of SD Negeri 2 Bayongbong and parents of students. This training begins with equalizing perceptions, presentation of materials, and practices in the form of digitalization simulations until they are distributed to students. The evaluation of this activity shows that this training can make it easier for teachers to prepare literacy materials and teaching materials so that they can succeed in the formation of student character. It is hoped that the teachers will succeed in GLS so that they can shape the character of students. Abstrak Pembentukan karakter siswa disangsikan keberhasilannya dalam pembelajaran di masa pandemi saat ini. Belajar dari rumah (BDR) membuat guru terbatas dalam melaksanakan pembelajaran serta pembentukan karakter siswa. Salah satu langkah positif yaitu dengan Gerakan Literasi Sekolah (GLS). Kesuksesan kegiatan literasi ini tentu akan berhasil atas kerjasama guru dan orang tua siswa untuk membudayakan dan menyediakan kegiatan literasi. Pelatihan ini berfokus pada keterampilan guru mendigitalisasi dan pemanfaatan aplikasi untuk menyediakan bahan literasi yang dapat merangsang pembentukan karakter siswa. Metode pelaksaanaan pelatihan ini ialah pendahuluan, pelatihan, praktik, dan simulasi. Objek kegiatan ini ialah para guru SD Negeri 2 Bayongbong dan orang tua siswa. Pelatihan ini, dimulai dengan penyamaan persepsi, pemaparan materi, dan praktik berupa simulasi digitalisasi hingga penyebarannya kepada siswa. Evaluasi kegiatan ini menunjukan bahwa pelatihan ini dapat mempermudah guru menyiapkan bahan literasi dan bahan ajar sehingga dapat menyukseskan pembentukan karakter siswa. Diharapkan para guru menyukseskan GLS sehingga dapat membentuk karakter siswa.